Pendampingan Pembuatan NIB UMKM melalui Sistem Online Single Submission (OSS) di Kelurahan Karangtengah - Alfina Rahma Nazilal Mubarok; Annisya Dellia Safitri; Fatiya Nur Aisyah; Gusti Putu Devandra Yudhistira; Radhiya Esa Fitriawati; Dewi Puspa Arum (FKIP, Universitas Palangka Raya, 2023)
Legality is the identity of a business to legalize a business so that it can be recognized by the public. Business legality is very important for Micro, Small and Medium Enterprises (MSMEs) because it can provide many benefits. To obtain complete and legal business legality, MSMEs must fulfill all applicable legal and regulatory requirements. The Thematic Real Work Lecture (KKNT) activities for MSMEs in Karangtengah Village involve several MSMEs that have been recorded and surveyed. The purpose of this community empowerment program itself is so that business actors can better understand the importance of NIB and can take advantage of government programs that can facilitate online legality permits. After registering business legality, it is hoped that business actors will consider the importance of licensing business entities, there needs to be more attention to training and socialization of business licensing in Karangtengah Village.